Combination therapy with lercanidipine and enalapril in the management of the hypertensive patient: an update of the evidence - Antza, Christina (Vasc Health Risk Manag, 2016)
Hypertension is an important risk factor for premature death as it increases the probability of stroke, myocardial infarction, and heart failure. Antihypertensive drugs can decrease cardiovascular (CV) morbidity and mortality. The majority of hypertensive patients need more than one antihypertensive agent to attain blood pressure (BP) targets. Monotherapy can effectively reduce BP only in 20%–40% of patients. Multiple mechanisms including increased peripheral vascular resistance, increased cardiac work, and hypervolemia are involved in the pathogenesis of hypertension. Targeting multiple pathways may more potently reduce BP. Increasing the dose of a single agent in many cases does not provide the expected BP-lowering effect because the underlying mechanism of the BP increase is either different or already corrected with the lower dose. Moreover, drugs acting on different pathways may have synergistic effects and thus better control hypertension. It is well known that diuretics enhance the actions of renin–angiotensin aldosterone system and activate it as a feedback to the reduced circulated blood volume. The addition of a renin–angiotensin aldosterone system blocker to a diuretic may more effectively reduce BP because the system is upregulated. Reducing the maximal dose of an agent may also reduce possible side effects if they are dose dependent. The increased prevalence of peripheral edema with higher doses of calcium channel blockers (CCBs) is reduced when renin–angiotensin aldosterone system blockers are added to CCBs through vein dilation. The effectiveness of the combination of enalapril with lercanidipine in reducing BP, the safety profile, and the use of the combination of angiotensin-converting enzyme inhibitors with CCBs in clinical trials with excellent CV hard end point outcomes make this combination a promising therapy in the treatment of hypertension.